Synthesize And Characterization Of Bioactive Glass Powder Based On Sio2-Cao-Na2o-P2o5 System - Ibrahim, Nurul Farhana (2019)
Bioactive glass (BG) powder have been used as a filler in bone defects due to the ability to connect with bone tissue through bonding formation with apatite layer. However, higher melting temperature (1450 °C-1570 °C) or longer soaking time (3 hours) is required to produce BG powder via conventional glass melting route. In this research work, new composition (50S8P, Nc =2.69), (54S4P, Nc =2.60) and (46S0P, Nc =1.62) of bioactive glass powder was developed from SiO2-CaO-Na2O-P2O5 system to obtain good processing and biological properties. The BG preparations included batching, mixing, melting at different temperature, water quench, milling and sieving. BG with 45S5 composition was used as a control. X-ray diffraction (XRD) revealed that fully amorphous glass structure was obtained for all BG composition with broad peaks between 30-35°. Silica network based glass was also confirmed through Fourier transform infrared spectroscopy (FTIR) with Si-O-Si (tetrahedral) functional group was observed in the spectrum. Thermal analysis proved that all BG composition can be melted at lower temperature where 45S5 at 1377 °C, 50S8P and 54S4P at 1348 °C with 46S0P at 1347 °C. Hence, the effect of different melting temperature and time (1.5, 1 and 0.5 hour) were also studied. Amorphous structure was still retained based on XRD although BG powder was synthesized with lower melting temperature at shorter melting time, 0.5 hour for all BG composition. The BG bioactivity was evaluated by incubating the BG powder with Tris buffer solution (pH 8) for 7, 14 and 21 days. In vitro test confirmed on the hydroxylapatite (HA) formation on the BG surface with emerging of crystalline peaks in XRD. Characteristic of carbonate (C-O) and phosphate (P-O) functional group noticed in FTIR with more intense peaks was observed on 45S5 and 50S8P BG compared to 54S4P and 46S0P BG. Better biological responds was observed on BG synthesized at 1400 °C upon incubation and was further evaluated by in vitro test in simulated body fluid (SBF), pH 7.3 and cell culture. However, less intense HA characteristic was observed in XRD and FTIR on the BG surface upon immersion in SBF compared to Tris buffer solution. Good compatibility was observed when dental pulp stem cell (DPSC) was exposed to all BG composition. In conclusion, new composition of BG powder was successfully developed at lower melting temperature and soaking time with good biological properties although possess high network connectivity.